Gerakan NPC Pada Game Pengenalan Huruf Menggunakan Algoritma Dijkstra - Nestia Febriyani Putri; Anang Kukuh Adisusilo (Informatics Engineering Department-UWKS, 2016)
Game is a game of electronic media is a means of entertainment and learning for all ages. Display dibauat games are usually attractive and interactive maingkin. Especially for learning games for children should be attractive and easy to understand and in terms edukasinya. In addition to the main character played by a companion character commonly called NPC (non-player character). In regulating the movement of NPC in the game to get to the target or the main characters are frequently experienced problems. Pathfinding is the method sanagt support to facilitate the movement of NPC in finding a primary target. Pathfinding algorithm which in dulaing dijkstra very suitable for giving Artificial Intelligence at the NPC. Dijkstra exact calculation algorithm by calculating the entire area to find the shortest distance to the target. In accordance manifold tower defense game is very suitable to use algorithms dijkstra for his NPC movement in butkitkan with smooth motion NPC without experiencing errors and delays in the movement of the NPC.